Advertising Information, Advertising Precision and Resale Price Maintenance - Wu, Sheng-Yeh; Lin, Suli; Chen, Guan-Ru; Hsu, Kai-Chi; Heish, Liang-Yu (Journal of Applied Business and Economics, 2019)
As consumers use the retail price as an estimator of product quality, the producer expects the retail price to efficiently signal the quality information. However, in the presence of price competition among retailers, consumers cannot predict quality by observing prices because they cannot identify whether the price discounts result from quality downgrade, or just retail supply’s increase. Since market price movements send noises over quality judgement, the producer uses resale price maintenance to control noises from retail supply. When resale price maintenance is prohibited by antitrust law, a rational expectations model predicts that the manufacturer can replace resale price maintenance with advertising.